Determination of Polypropylene Fiber-Reinforced Concrete Compressive Strength and Elasticity Modulus via Ultrasonic Pulse Tests - Del Savio, Alexandre Almeida (2022)
Compressive strength and elasticity modulus are the main mechanical properties of concrete. The non-destructive ultrasound pulse test can be used to determine these properties without compromising the structure’s integrity. This study seeks to assess whether a correlation exists (1) between the Reinforcement Index (RI) and the mechanical properties, (2) between the RI and the dynamic properties, and (3) among the dynamic properties of polypropylene fiber-reinforced concrete. The RI was modified through fiber volume fraction (0, 0.4, 0.8 and 1.2%) and fiber length (40, 50 and 60 mm). The dynamic properties were assessed through dynamic elasticity modulus and ultrasonic pulse velocity (UPV), which were determined by direct, semi-direct, and indirect prospect methods. Finally, compressive strength, static elasticity modulus, and Poisson’s ratio were assessed through destructive tests. Their relationship with UPV and the dynamic elasticity modulus is also subsequently studied. The results reveal a correlation between RI and compressive strength and UPV; however, the static elasticity modulus only exhibits a correlation with UPV in one of its measurement methods. Finally, empirical models were developed for predicting compressive strength, elasticity modulus as a function of ultrasonic pulse velocity and RI, and dynamic elasticity modulus as a function of compressive strength and RI.